Effects of citrus limon essential oil (Citrus limon L.) on cytomorphometric changes of Candida albicans - Rina Prabajati; Iwan Hernawan; Hening Tuti Hendarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: The most common fungal infection found in oral cavity is oral candidiasis, largely caused by Candida species, particularly Candida albicans (C. albicans). Candida infection can get worse since it is difficult to be treated and resistant with antifungal drugs. Therefore, new drugs and compounds as well as alternative therapies involving natural sources that have antifungal activities have continually been developed. Limonene, β-pinene, and ɣ-terpinene contained in Citrus limon essential oil have been known to have quite good antifungal activities against C. albicans. Purpose: This research aimed to examine and analyze the effects of Citrus limon essential oil on cytomorphometric changes of C. albicans. Method: The research used post test only control group design. Based on the results of the pre-elementary research on antifungal activities of Citrus limon essential oil against C. albicans, Citrus limon essential oil used in this research was on concentrations of 1.56%, 1.37%, 1.17%, 0.98%, and 0.78%. Citrus limon essential oil by C. albicans inoculum and incubated for 24 hours and 48 hours. After the incubation, those C. albicans cells were fixed, dried, and then observed using a scanning electron microscopy. Result: The most effective concentrations of Citrus limon essential oil triggering cytomorphometric changes of Candida albicans were at 1.37% and 1.56% with the incubation period of 48 hours. Conclusion: C. albicans can undergo necrosis process through cytomorphometric changes after the administration of Citrus limon essential oil at concentrations of 1.56% and 1.37% with the incubation period of 48 hours.